Clinical insights on nutrition support in pediatric cancer care: a survey of pediatric oncologists - Sripriya Venkiteswaran; Sangeeta Mudaliar; Purvi Kadakia; Uma Seshadri; Purnota D. Bahl; Anju Morarka (International Journal of Contemporary Pediatrics, 2026)
Cuddles Foundation, an NGO in India providing comprehensive nutrition care to children with cancer, conducted a nationwide survey among pediatric oncology professionals to understand the perceived impact of nutrition intervention programs on clinical outcomes, treatment tolerance, and caregiver empowerment for pediatric oncology patients. Responses from 48 pediatric oncology doctors, including residents, consultants, and department heads, revealed overwhelmingly positive perceptions of nutrition in improving patient outcomes.